Hubungan fungsi motorik dan derajat kekuatan otot dengan kejadian fatigue pasca stroke - Putu Yogi Pramana; Cokorda Istri Dyah Sintarani Sintarani; Ida Ayu Sri Wijayanti Wijayanti; Anak Agung Raka Sudewi Sudewi (DiscoverSys Inc., 2022)
Background: Fatigue is an experience in the form of fatigue that is often experienced by post-stroke patients. Pharmacological therapy used in the treatment of post-stroke fatigue has not been effective in treating fatigue. Several studies also mention the presence of impaired motor function and a decrease in the degree of strength in post-stroke patients, which causes patients to avoid physical activity, causing fatigue. The purpose of this study was to determine the relationship between motor function and the degree of muscle strength with post-stroke fatigue. Method: This analytic observational study with the Pearson correlation test was conducted using a questionnaire, examined and collected data from the register of outpatients at the Neurology Polyclinic of Dharma Yadnya General Hospital, Denpasar, from March to May 2022. Fatigue was assessed using a Fatigue Severity Scale questionnaire, and motor function was assessed using the Fatigue Severity Scale questionnaire. Pulg Meyer questionnaire. The significance level of the relationship was assessed by chi-square, and the strength of the relationship was assessed by the Pearson correlation test. Result: There were 82 sample subjects. 46 subjects (60%) experienced fatigue, and 36 (40%) subjects did not experience fatigue. With the Pearson correlation test, it was found that there was a significant relationship between motor function and the degree of muscle strength with post-stroke fatigue with a value of (r) 0.712 and (r) 0.527.Conclusion: There is a significant relationship between motor function and the degree of muscle strength with post-stroke fatigue. Latar Belakang: Fatigue merupakan suatu pengalaman subjektif berupa perasaan kelelahan yang sering dialami oleh pada pasien pasca stroke. Terapi farmakologi yang digunakan dalam penanganan fatigue pasca stroke selama ini masih belum efektif dalam penanganan fatigue. Beberapa studi juga menyebutkan dengan adanya gangguan fungsi motorik dan penurunan derajat kekuatan otot pada pasien pasca stroke menyebabkan pasien cenderung menghindari aktivitas fisik sehingga menimbulkan terjadinya fatigue. Tujuan penelitian ini adalah untuk mengetahui hubungan dari fungsi motorik dan derajat kekuatan otot dengan fatigue pasca stroke. Metode: Studi observasional analitik dengan uji korelasi pearson ini dilakukan dengan menggunakan kuisioner, melakukan pemeriksaan dan mengumpulkan data dari register pasien yang dirawat jalan di Poli Saraf Rumah Sakit Umum Dharma Yadnya, Denpasar dari Maret hingga Mei 2022. Fatigue dinilai menggunakan kuisioner Fatigue Severity Scale dan fungsi motorik dinilai menggunakan kuisioner Pulg Meyer.Tingkat kemaknaan hubungan dinilai dengan chi-square dan kekuatan hubungan dinilai dengan uji korelasi Pearson. Hasil: terdapat 82 subjek sampel, didapatkan subjek yang mengalami fatigue sebesar 46 subjek (60%) dan 36 subjek (40%) tidak mengalami fatigue. Dengan uji korelasi pearson didapatkan adanya hubungan bermakna antara fungsi motorik dan derajat kekuatan otot dengan fatigue pasca stroke dengan nilai (r) 0,712 dan (r) 0,527. Kesimpulan: Terdapat hubungan bermakna antara fungsi motorik dan derajat kekuatan otot dengan fatigue pasca stroke.